2023
DOI: 10.1049/enc2.12093
|View full text |Cite
|
Sign up to set email alerts
|

A data‐driven method for microgrid bidding optimization in electricity market

Rudai Yan,
Yan Xu

Abstract: This paper presents a deep reinforcement learning based data‐driven solution to the microgrid bidding in the electricity market considering offers for the reserve market. The framework, based on the Markov decision process, models the microgrid's participation in the electricity market at different stages, including bidding, market‐clearing, and reserve activation. The problem is split into two stages: day‐ahead submission and real‐time market period, and the proposed method mainly focus on the first stage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…a microgrid) [6,7] or hybrid systems [8] with renewables, including PV and ESS, as well as other resources, which cannot be directly applied to the power bidding problem. A recent study [9] reported a data-driven method for energy bidding in the electricity market; however, this method was designed for a microgrid, not for the case in this study.…”
Section: Xumentioning
confidence: 99%
“…a microgrid) [6,7] or hybrid systems [8] with renewables, including PV and ESS, as well as other resources, which cannot be directly applied to the power bidding problem. A recent study [9] reported a data-driven method for energy bidding in the electricity market; however, this method was designed for a microgrid, not for the case in this study.…”
Section: Xumentioning
confidence: 99%